KAJIAN RETENSI KAROTEN KAPANG ONCOM MERAH DARI TONGKOL JAGUNG SELAMA PENGOLAHAN DAN PENYIMPANAN MIE INSTAN FUNGSIONAL - Nurakhirawati Nurakhirawati; Harianthy Aneke; Syaiful Bahri (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
Has done research on carotenoids retention oncom red on the processing and storage of instant noodles functional.This study aims was to determine the level of damage carotene in the instant noodle processing and to determine the carotene retention during storage of instant noodles as well as to determine the shelf life of instant noodles at a temperature 50ºC and 60ºC. Estimation of shelf life or expiration period using the model of reaction kinetics the treatment phase of the study include red oncom mold production, processing instant noodles and storage of instant noodles on the temperature. Analysis carotene on instant noodlesdone every 0 days to 6 days using UV-Vis spectrophotometry method in wavelength. The data obtained is used to determine the shelf life of instant noodles. The results obtained showed live carotene demage during the processing of instant noodles is to 20g = 1,867%. For temperature 60oC for 20g = 10,208%, and determining Q10 is 2,90 and the expiration of a functional instant noodles is 122 days.Keywords : Carotene, Mie Functional, Retention carotene, Shelf life, Reaction Kinetics Model